A chest patch for continuous vital sign monitoring: clinical validation study during movement and controlled hypoxia - Morgado Areia, C; Santos, M; Vollam, S; Pimentel, M; Young, L; Roman, C; Ede, J; Piper, P; King, E; Gustafson, O; Harford, M; Shah, A; et al. (JMIR Publications, 2021)
Background: The standard of care in general wards includes periodic manual measurements, with the data entered into track-and-trigger charts, either on paper or electronically. Wearable devices may support health care staff, improve patient safety, and promote early deterioration detection in the interval between periodic measurements. However, regulatory standards for ambulatory cardiac monitors estimating heart rate (HR) and respiratory rate (RR) do not specify performance criteria during patient movement or clinical conditions in which the patient’s oxygen saturation varies. Therefore, further validation is required before clinical implementation and deployment of any wearable system that provides continuous vital sign measurements.